2019
DOI: 10.3390/cells8091029
|View full text |Cite
|
Sign up to set email alerts
|

β-Aminobutyric Acid Priming Acquisition and Defense Response of Mango Fruit to Colletotrichum gloeosporioides Infection Based on Quantitative Proteomics

Abstract: β-aminobutyric acid (BABA) is a new environmentally friendly agent to induce disease resistance by priming of defense in plants. However, molecular mechanisms underlying BABA-induced priming defense are not fully understood. Here, comprehensive analysis of priming mechanism of BABA-induced resistance was investigated based on mango-Colletotrichum gloeosporioides interaction system using iTRAQ-based proteome approach. Results showed that BABA treatments effectively inhibited the expansion of anthracnose caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 65 publications
1
18
0
1
Order By: Relevance
“…The accelerated glycolysis pathway induced by the X33 antifungal extract might be favored for providing more backbone for other anabolism processes. This is according to a previous study, which reported that β-aminobutyric acid treatment upregulated several proteins involved in the glycolysis pathway, while no significant changes in the ATP synthesis of mango fruit were identified (Li et al, 2019).…”
Section: Energy Metabolism In P Digitatum Induced By the X33 Antifunsupporting
confidence: 88%
“…The accelerated glycolysis pathway induced by the X33 antifungal extract might be favored for providing more backbone for other anabolism processes. This is according to a previous study, which reported that β-aminobutyric acid treatment upregulated several proteins involved in the glycolysis pathway, while no significant changes in the ATP synthesis of mango fruit were identified (Li et al, 2019).…”
Section: Energy Metabolism In P Digitatum Induced By the X33 Antifunsupporting
confidence: 88%
“…In Albania and Italy, winds and drought were identified as the stress factors predisposing the host-plant to the infections by Colletotrichum spp. and allowing these ubiquitous fungi to switch from a endophytic or saprophytic to a pathogenic lifestyle, while in California the predisposing stress factors have not yet been precisely determined [ 5 , 52 ]. A better understanding of both the diversity of Colletotrichum species, associated with twig and shoot dieback of citrus, and the factors triggering the outbreaks of this disease is basilar for developing effective management strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the OX-induced and the BTH or BABA-induced plant disease resistance have similarities and differences. Literature shows that BTH or BABA can induce the plant broad-spectrum disease resistance [19][20][21][22][23][24][25]. For instance, BTH can induce the plant disease resistance against turnip crinkle virus, Peronospora parasitica, and Pst DC3000 in Arabidopsis [19].…”
Section: Discussionmentioning
confidence: 99%
“…radicis-lycopersic in Solanum lycopersicum [20], and Botrytis cinerea in Vitis vinifera [21]. BABA, a nonprotein amino acid, can induce the plant disease resistance in many plants against different pathogens, such as the B. cinerea and P. parasitica in Arabidopsis [22,23], Plasmopara viticola in Vitis vinifera [24], and Colletotrichum gloeosporioides in Mangifera indica [25]. Plant disease resistance can also be activated by beneficial microbes.…”
Section: Introductionmentioning
confidence: 99%